Artificial fruit for monitoring the thermal history of horticultural produce in the cold chain. (December 2017) - Defraeye, Thijs; Wu, Wentao; Prawiranto, Kevin; Fortunato, Giuseppino; Kemp, Shelley; Hartmann, Stefan; Cronje, Paul; Verboven, Pieter; Nicolai, Bart
Abstract: There is a need for more realistic monitoring of fruit pulp temperature history throughout the cold chain at a higher spatial resolution inside the cargo. Particularly solutions that are easy to install in a commercial setting are required. For this purpose, a novel kind of fruit simulator – an artificial fruit – has been designed, manufactured and tested. Using a biomimetic approach, it was engineered specifically to match the thermal response of real fruit as close as possible. The artificial fruit is composed out of a thin plastic shell, which mimics the exterior size, shape, surface texture and color of the fruit of interest. This shell is filled with a mixture that has similar thermal properties as real fruit as it is basically composed out of the same components. Two self-powered data loggers with a built-in sensor are integrated in the artificial fruit. These different components of the artificial fruit were combined successfully into a manufactured prototype. The thermal response of an artificial apple fruit during cooling was evaluated against that of 10 real apples. The cooling time of the artificial fruit was within 5% of that of the real fruits. The artificial fruit also had a more accurate thermal response than that of water-filled fruit simulators, with which differences up to 16% were found. The uniformity in size, shape and sensor location of the artificial fruit also enables it to measure fruit pulp temperature in a much more repeatable manner than with real fruit. A particular advantage of the artificial fruit is that it can be packed directly with the fresh produce in a commercial setting, by which multiple locations inside the cargo can easily be monitored. This novel sensor system thus provides an improved method to identify heterogeneities in cargo cooling, and associated quality issues. The artificial fruit is especially of interest for monitoring fruit pulp in precooling facilities, cold stores, ripening facilities and refrigerated containers. Highlights: A new fruit simulator was engineered to closely match the thermal response of real fruit. The artificial fruit can monitor fruit pulp thermal history throughout the entire cold chain. The artificial fruit reacts thermally very similar to real fruit. The artificial fruit can be packed directly with the fresh produce in a commercial setting. An improved method to identify heterogeneities in cargo cooling, and associated quality issues.